Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find the roots of the quadratic equation [tex]\(2x^2 + 8x + 7 = 0\)[/tex], we can use the quadratic formula, which is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, the coefficients are [tex]\(a = 2\)[/tex], [tex]\(b = 8\)[/tex], and [tex]\(c = 7\)[/tex].
First, we need to calculate the discriminant, which is [tex]\(b^2 - 4ac\)[/tex]:
[tex]\[ \text{Discriminant} = b^2 - 4ac = 8^2 - 4 \cdot 2 \cdot 7 = 64 - 56 = 8 \][/tex]
So, the discriminant is [tex]\(8\)[/tex].
Next, we use the quadratic formula to find the roots:
[tex]\[ x = \frac{-b \pm \sqrt{\text{Discriminant}}}{2a} = \frac{-8 \pm \sqrt{8}}{2 \cdot 2} = \frac{-8 \pm \sqrt{8}}{4} \][/tex]
Let's simplify [tex]\(\sqrt{8}\)[/tex]:
[tex]\[ \sqrt{8} = \sqrt{4 \cdot 2} = 2\sqrt{2} \][/tex]
Now, we substitute [tex]\(\sqrt{8}\)[/tex] with [tex]\(2\sqrt{2}\)[/tex] in the quadratic formula:
[tex]\[ x = \frac{-8 \pm 2\sqrt{2}}{4} = \frac{-8}{4} \pm \frac{2\sqrt{2}}{4} = -2 \pm \frac{\sqrt{2}}{2} \][/tex]
Upon further simplification:
[tex]\[ x = -2 \pm \frac{\sqrt{2}}{2} \][/tex]
This gives us two roots:
[tex]\[ x_1 = -2 + \frac{\sqrt{2}}{2} \][/tex]
And
[tex]\[ x_2 = -2 - \frac{\sqrt{2}}{2} \][/tex]
From the given options, the correct answer matches the simplified form:
D. [tex]\( x = \frac{-2 \pm \sqrt{2}}{1} \)[/tex]
Hence, the correct answer is:
D. [tex]\(x = \frac{-2 \pm \sqrt{2}}{1}\)[/tex]
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, the coefficients are [tex]\(a = 2\)[/tex], [tex]\(b = 8\)[/tex], and [tex]\(c = 7\)[/tex].
First, we need to calculate the discriminant, which is [tex]\(b^2 - 4ac\)[/tex]:
[tex]\[ \text{Discriminant} = b^2 - 4ac = 8^2 - 4 \cdot 2 \cdot 7 = 64 - 56 = 8 \][/tex]
So, the discriminant is [tex]\(8\)[/tex].
Next, we use the quadratic formula to find the roots:
[tex]\[ x = \frac{-b \pm \sqrt{\text{Discriminant}}}{2a} = \frac{-8 \pm \sqrt{8}}{2 \cdot 2} = \frac{-8 \pm \sqrt{8}}{4} \][/tex]
Let's simplify [tex]\(\sqrt{8}\)[/tex]:
[tex]\[ \sqrt{8} = \sqrt{4 \cdot 2} = 2\sqrt{2} \][/tex]
Now, we substitute [tex]\(\sqrt{8}\)[/tex] with [tex]\(2\sqrt{2}\)[/tex] in the quadratic formula:
[tex]\[ x = \frac{-8 \pm 2\sqrt{2}}{4} = \frac{-8}{4} \pm \frac{2\sqrt{2}}{4} = -2 \pm \frac{\sqrt{2}}{2} \][/tex]
Upon further simplification:
[tex]\[ x = -2 \pm \frac{\sqrt{2}}{2} \][/tex]
This gives us two roots:
[tex]\[ x_1 = -2 + \frac{\sqrt{2}}{2} \][/tex]
And
[tex]\[ x_2 = -2 - \frac{\sqrt{2}}{2} \][/tex]
From the given options, the correct answer matches the simplified form:
D. [tex]\( x = \frac{-2 \pm \sqrt{2}}{1} \)[/tex]
Hence, the correct answer is:
D. [tex]\(x = \frac{-2 \pm \sqrt{2}}{1}\)[/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.